Association analysis uncovers the genetic basis of general combining ability of 11 yield-related traits in parents of hybrid rice. Issue 1 (18th December 2018) - Ullah Zaid, Imdad; Tang, Weijie; He, Jianbo; Ullah Khan, Sana; Hong, Delin
Abstract: Association analysis between constructed single nucleotide polymorphism linkage disequilibrium blocks (SNPLDBs) and general combining ability (GCA) effects is a novel approach to uncover the genetic basis of GCA within the sequence genomes of parents of hybrid rice. Here, we calculated the GCA effect values of 33 parents of hybrid rice and sequenced them to identify genome-wide single nucleotide polymorphisms (SNPs). In total, 64.6 % of the uniquely mapped paired-end short reads revealed a final total of 291 959 SNPs between the 33 parental genomes and the Nipponbare reference genome. The identified SNPs were non-randomly distributed among all chromosomes of rice, whereas one-fourth of the SNPs were situated in the exonic regions with 16 % being non-synonymous. Further, the identified SNPs were merged and optimized for construction of 2612 SNPLDB markers, using linkage disequilibrium information. The single-factor analysis of variance-based association method between the constructed SNPLDB markers and GCA effects values detected 99 significant SNPLDBs for GCA of 11 yield-related traits. The associated SNPLDB markers explained 26.4 % of phenotypic variations with traits, on average. We mined 50 favourable GCA alleles at the associated SNPLDBs regions, distributed across the 33 parental genomes. The parental genomes possessed a small number of favourable GCA alleles for studied traits, with the exception of days to heading and plant height. Our results suggest that the identified GCA alleles could be used to improve the GCA performance of parents of hybrid rice through optimal crossing design. Moreover, favourable GCA alleles should be incorporated in the parental genomes through marker-assisted selection experiments, and the parental lines carrying more alleles could be utilized in breeding as superior parents for developing rice hybrids of desirable characteristics. Abstract : We calculated the GCA values of 33 parents of hybrid rice and sequenced them to identify SNPs. In total, 64.6 % of the uniquely mapped paired-end reads revealed a final total of 291 959 SNPs between the 33 parents and the Nipponbare reference. The identified SNPs were non-randomly distributed, whereas one-fourth of the SNPs were situated in the exonic regions with 16 % being non-synonymous. The identified SNPs were optimized for construction of 2612 SNPLDB markers, using linkage disequilibrium. The association between SNPLDB markers and GCA values detected 99 significant SNPLDBs of GCA having 26.4 % of phenotypic variations.